2020
DOI: 10.1016/j.bbmt.2019.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Basiliximab as Treatment for Steroid-Refractory Acute Graft-versus-Host Disease in Pediatric Patients after Haploidentical Hematopoietic Stem Cell Transplantation

Abstract: Basiliximab has been used successfully as a second-line treatment for steroid-refractory (SR) acute graft-versushost disease (aGVHD) in adult patients after haploidentical hematopoietic stem cell transplant (haplo-HSCT) but has not been studied separately in the pediatric setting. We retrospectively reviewed 100 pediatric patients after haplo-HSCT receiving basiliximab for grades II (57%), III (27%), and IV (16%) SR aGVHD between January 2015 and December 2017. The median number of basiliximab doses was 4 (ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 36 publications
3
30
0
Order By: Relevance
“…Myeloid and platelet engraftment were defined according to previous reports 5,13 . Hematopoietic chimerism was evaluated by PCR amplification of STRs for all patients using peripheral blood samples and buccal mucosa and by FISH for sex‐mismatched pairs using BM samples.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Myeloid and platelet engraftment were defined according to previous reports 5,13 . Hematopoietic chimerism was evaluated by PCR amplification of STRs for all patients using peripheral blood samples and buccal mucosa and by FISH for sex‐mismatched pairs using BM samples.…”
Section: Methodsmentioning
confidence: 99%
“…7,12 The standard initial therapy for aGVHD is corticosteroids; only approximately 50% of patients demonstrate responses. 13,14 The standard second-line agent for the treatment of SR-aGVHD is not clear, and no consensus has been reached, including in pediatric patients. 15,16 aGVHD in pediatric TCR haplo-HSCT without PT-Cy has been reported in previous studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infections occurred in 65% of patients in this study; 48% of patients were alive after a mean follow-up of 2 years. Several subsequent studies also showed high ORRs (82-92%), including in pediatric patients; however,~50-70% of patients experienced GVHD recurrence, and rates of infectious complications were high [21,[57][58][59]. Kaplan-Meier-estimated probabilities were 48% for 3-year event-free survival and 20% for 5-year OS [21,57].…”
Section: Antibodies Against Il-2r: Basiliximabmentioning
confidence: 94%
“…Approved biosimilars of rituximab (Reditux ® , Rixathon ® , Ruxience ® and others) seem to have similar infection rates with rituximab, even though data for IFDs are currently lacking [50]. 90 Y-ibritumomab tiuxetan, as stated above, is associated with more severe leukopenia, possibly due to radiation effects on cells surrounding CD20+ targets. Nevertheless, the spectrum of infections is similar to that of rituximab [41].…”
Section: Targeting Antigens On Lymphoid Cellsmentioning
confidence: 98%